(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Continuous renal replacement therapy (CRRT) is an effective dialysis method in critically ill patients. Citrate and heparin are commonly used as anticoagulants to prevent premature circuit clotting. The aim of this study was to evaluate the safety and efficacy of using low dose systemic heparin while on CRRT in liver transplant recipients. Methods. We retrospectively evaluated and analyzed data from 29 liver transplant recipients undergoing CRRT in the postoperative course in this cross-sectional study. Numerous variables were recorded, such as coagulation parameters, duration of intensive care unit (ICU) stay, duration of dialysis, heparin dose, circuit life span, and anticoagulant complications. Results. Out of 29 recipients, there were 16 (55%) female and 13 (45%) male. All participants underwent whole organ liver transplantation with a median age of 45 years. Overall, 98 successful dialysis sessions were recorded in this study with a mean circuit life span of 36 hours. Mean ± SD duration of CRRT for each recipient was 4.8 ± 3.1 days. The median total dose of heparin used for each recipient was 25,000 units , and the median dose of heparin per-day for each recipient was about 3,300 units. There were no episodes of anticoagulant-related bleeding complications. Thirteen (13.2%) episodes of premature circuit clotting occurred. We found a significant association between the first dose and total dose of heparin usage with first postoperative INR and PTT level (P < .05, P < .05, P < .001, and P < .05). Conclusion. In liver transplant recipients, low dose heparin during CRRT for patency of circuit is well tolerated.